Oxidized low density lipoproteins induce apoptosis in human lymphocytes: involvement of mitogen-activated protein kinases - Bustamante, M.; Diaz, F.; Muñoz, M.; Gross, H-J.; Rivas, C.I.; Llancaqueo, A.; Núñez, L.; Campos, L.; Kirsten, L.; Grandón, J.; González, M.; Barra, V.; et al. (Cellular and Molecular Biology, 2007)
Oxidized low density lipoproteins (oxLDL), macrophages and T-lymphocytes are present in atherosclerotic lesions. We and others have shown that oxLDL is cytotoxic for macrophages, endothelial, smooth muscle and activated T-lymphocytes and induce apoptosis. Here we demonstrate that (i) oxidized LDL (oxLDL), oxidized VLDL (oxVLDL) and hydrogen peroxide (H2O2) induce apoptosis in human T-lymphocytes and (ii) mitogen-activated protein kinases are involved in this process. Apoptosis was monitored by immunofluorescence microscopy and flow cytometry for annexin V binding, Apo 2.7 expression, the TUNEL reaction and caspase 3 activity. In the presence of oxLDL (100 microg/ml), oxVLDL (50 microg/ml) and H2O2 (5 mM), the fraction of apoptotic cells increased within 6 hours to more than 70%. Preincubation of lymphocytes with the MAPKK inhibitor PD-98059 and the p38MAPK inhibitor SB-203580 almost completely abolished these effects. Furthermore, oxLDL and H2O2 but not native LDL strongly enhanced phosphorylation of JNK, p38MAPK and p42/44MAPK. The results suggest that in the resting lymphocyte apoptosis triggered by oxidized lipoproteins and oxidative stress depends on the activation of p44/42MAPK and p38MAPK cascades.